Modeling Optimal Debt and Expenditure in Malawi: A Dynamic Optimization Approach - ADEDOKUN, Adebayo; BABATUNDE, Ololade Moses (Asian Journal of Economic Modelling, 2017)
This study models optimal debt and spending in Malawi using Dynamic Optimization Approaches. The study found that the economy of Malawi is not free from debt crisis, despite the benefits of Multilateral Debt Relief Initiative (MDRI) that was extended to Heavily Indebted Poor Countries (HIPC) in 2005. The optimal trends show that the country has been and remains vulnerable to debt and fiscal crises despite the various palliative measures that were introduced by International Monetary Funds (IMF), especially the Extended Credit Facility (ECF) offered the country in 2008, during the global financial crises.